2021
DOI: 10.3389/fnsyn.2021.799274
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Type-Specific Adaptions in Striatal Medium-Sized Spiny Neurons and Their Roles in Behavioral Responses to Drugs of Abuse

Abstract: Drug addiction is defined as a compulsive pattern of drug-seeking- and taking- behavior, with recurrent episodes of abstinence and relapse, and a loss of control despite negative consequences. Addictive drugs promote reinforcement by increasing dopamine in the mesocorticolimbic system, which alters excitatory glutamate transmission within the reward circuitry, thereby hijacking reward processing. Within the reward circuitry, the striatum is a key target structure of drugs of abuse since it is at the crossroad … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 206 publications
1
12
0
Order By: Relevance
“…Traditionally, SPNs have been segregated into two subpopulations based on expression of D1like or D2-like receptors [12][13][14] . Indeed, SPNs expressing D1-like receptors differ from SPNs that express D2-like receptors at cellular, circuit, and behavioral levels [15][16][17][18][19][20][21] . However, many questions remain concerning this dichotomous separation.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, SPNs have been segregated into two subpopulations based on expression of D1like or D2-like receptors [12][13][14] . Indeed, SPNs expressing D1-like receptors differ from SPNs that express D2-like receptors at cellular, circuit, and behavioral levels [15][16][17][18][19][20][21] . However, many questions remain concerning this dichotomous separation.…”
Section: Introductionmentioning
confidence: 99%
“…Given evidence of baseline and drug-stimulated compulsive behaviors in DAT Val559 mice and the ability of DA to modulate spine density of striatal medium spiny neurons (MSNs) [ 47 ], we hypothesized that DAT Val559-driven ADE might drive neuroadaptations in key brain regions linked to compulsions. Our prior studies demonstrated that perturbations in DAT trafficking and function were confined in DAT Val559 males to the dorsal striatum [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, it has become a consensus that there are sex differences in the incidence of dopamine-related neuropsychiatric disorders and sensitivity to dopamine-enhancing drugs such as stimulants, and previous studies have shown that dopaminergic circuits often act through dopamine receptors D1 and D2 (Fasano et al, 2013 ; Stalter et al, 2020 ; Allichon et al, 2021 ). It has been shown in the chronic constriction injury (CCI) pain model of the sciatic nerve in mice that dopaminergic projections from the VTA to the nucleus accumbens (NAc) are involved in pain modulation (Ding et al, 2021 ).…”
Section: Sex Differences In Neurotransmitters and Neuromodulatorsmentioning
confidence: 99%